FAKTOR–FAKTOR YANG MEMPENGARUHI SENSITIVITAS LABA PADA INDUSTRI BARANG KONSUMSI DI INDONESIA - Candra Romanda (Universitas muhammadiyah malang, 2012)
Candra Romanda, S.E., M.SiSTIE Rahmaniyah SekayuE-mail: c_romanda_mubalink@yahoo.co.idABSTRACTThe purpose of this study was to analyze the influence of conservative financial statements, thecompany’s life cycle, earnings growth, dividend payout ratio, default risk and size of the company’searnings response coefficients in the Consumer Goods Industry in Indonesia. The populationsare 32 consumption industrial enterprises which are listed in Indonesia Stock Exchange 2007 –2010. Respondent are 20 companies which were chosen by using purposive sampling. To knowwhether simultaneously the independent variables affect to earnings response coefficient usedthe F test and individually the t test. The results shown by the first model that conservatism didnot affect the financial statements of earnings response coefficients. In addition, there were nosignificant differences in market response to the tendency of financial reporting either a conservativeor optimistic. The company’s life cycle has positive and significant impact on earningsresponse coefficients and earnings response coefficients are the differences between the categoriesof corporate life cycle. Earnings growth has positive and significant impact on earningsresponse coefficients. Dividend payout ratio has no effect on earnings response coefficients,Default risk has no effect on earnings response coefficients, and company size has no effect onearnings response coefficients.Keywords: Earnings response coefficient, Financial Conservatism, Corporate Life Cycle, IncomeGrowth, Dividend Payout Ratio, Size of the Company, Default Risk.